A randomised assessment of the use of a quality of life questionnaire with or without intervention in patients attending a thoracic cancer clinic. (10th November 2015) - Nimako, K.; Ayite, B.; Priest, K.; Severn, J.; Fries, H.M.; Gunapala, R.; Bhosle, J.; Popat, S.; O'Brien, M.
Abstract : The study examined the impact of using a quality of life (QoL) questionnaire during a clinic to identify QoL issues and to improve QoL. 138 patients were randomised (1:1:1) to either (1) an Intervention group that completed the European Organisation for Research and Treatment of Cancer–Core Quality of Life Questionnaire and Lung Cancer Module (EORTC QLQ‐C30 and LC13) at baseline and received feedback during a clinic, (2) an Attention group that completed the questionnaire at baseline without feedback and (3) a Control group that did not complete the questionnaire. All patients completed the same questionnaire 6 weeks later and a contact diary during the study period. There was a significant difference between the Intervention and Control groups for the mean number of QoL issues identified at baseline (4.69 vs. 2.81, P = 0.006) and the mean number of actions taken (4.41 vs. 2.46, P = 0.004). At 6 weeks, there was no difference between the groups in global QoL (Intervention vs. Control group, P = 0.596; Attention vs. Control, P = 0.973). The results suggest that the completion of the EORTC QLQ‐C30 LC13 with feedback improves communication and increases the number of QoL issues identified and actions taken. However, the intervention does not impact on QoL per se . Clinicaltrials.gov: NCT01213745